One Health Approach Reveals the Absence of Methicillin-Resistant Staphylococcus aureus in Autochthonous Cattle and Their Environments - Correia, Susana (2020)
This work was funded by the R&D Project CAREBIO2 - Comparative assessment of antimicrobial resistance in environmental biofilms through proteomics - toward innovative theranostic biomarkers, with reference NORTE-01-0145-FEDER-030101 and PTDC/SAU-INF/30101/2017, the European Regional Development Fund (ERDF) through the Northern Regional Operational Program (NORTE 2020) and the Foundation for Science and Technology (FCT). Associate Laboratory for Green Chemistry -LAQV which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019). VS is supported by national funds through FCT/MCTES and by the European Social Fund through POCH/FSE under the PhD grant SFRH/BD/137947/2018.